Live to tell a detective D.D. Warren novel - Gardner, Lisa (New York Bantam Books, 2010)
On a warm summer night in one of Boston's working class neighborhoods, an unthinkable crime has been committed: Four members of a family have been brutally murdered. Murder-suicide? Or something worse? Danielle Burton is a survivor, a dedicated nurse whose passion is to help children at a locked-down pediatric psych ward. But she remains haunted by a family tragedy that shattered her life nearly twenty-five years ago. When D.D. Warren and her partner show up at the facility, Danielle immediately realizes: It has started again. A devoted mother, Victoria Oliver has a hard time remembering what normalcy is like. But she will do anything to ensure that her troubled son has some semblance of a childhood. She will love him no matter what. Nurture him. Protect him. Even when the threat comes from within her own house. The lives of these three women unfold and connect in unexpected ways, as sins from the past reveal just how tightly blood ties can bind.
96603
Keywords: Murder -- Investigation; Boston (Mass.); Mystery fiction; Suspense fiction